Urgensi Pembentukan Lembaga Pengawas Eksternal Yayasan di Indonesia Untuk Mengatasi Penyelewengan - Muhammad Ath-Thariq Pratama; Nurhidayah Muhcti; Nyulistiowati Suryanti; Deviana Yuanitasari (International Forum of Researchers and Lecturers, 2024)
This research examines the regulation of remuneration for Foundation executives in Indonesia, focusing on legal aspects and its implementation. As Foundations evolve to support social, religious, and humanitarian objectives, cases of misappropriation of Foundation funds have emerged, highlighting the need for tighter oversight. Through a normative juridical approach and descriptive analysis, this study details the issues surrounding remuneration regulations, emphasizes instances of financial misconduct, and discusses the importance of establishing an external supervisory body or regulatory changes. The implementation of Good Corporate Governance and Good Cooperative Governance principles within the Foundation context is also explored. This research responds to the need for integrity, transparency, and accountability in Foundation management to achieve the humanitarian goals they undertake. The conclusion underscores the necessity for further action, including the establishment of an external supervisory body or regulatory strengthening.